Political Islam: An Exploration of the Argument of Olivier Roy that Political Islam is a Failure in the Light of Two Muslim Majorities (Social Science Review, 2025)
The emergence of Political Islam has sparked expansive academic debates regarding its failure to acknowledge its intended goals, as argued by Olivier Roy (1994) in his seminal work. This paper aims to evaluate Roy's central argument by scrutinizing the fundamental motivations of Political Islam and its ramifications on two Muslim- majority countries - Egypt and Pakistan, both with a rich historical legacy of Political Islam. Consistent with Roy's analysis, this study finds that Political Islam can be considered a failure in light of these two Muslim majorities, based on the thesis of Roy. Given that Political Islam has been unsuccessful in accomplishing its objectives of capturing state power and transforming society, it underscores that the projects of Political Islam are self-contradictory and lack modern-day realist interpretations. Consequently, Political Islam has metamorphosed into an instrument for political elites who exploit Islamic ideals to conform their political ambitions.Social Science Review, Vol. 42(1), June 2025, pp. 113-128